COMMUNICATION CHALLENGES AND ADAPTIVE STRATEGIES AMONG INTERNATIONAL DOCTORAL STUDENTS IN THE UNITED STATES - Peixin Liu; Jalaluddin (STKIP Paracendekia NW Sumbawa, 2026)
This qualitative study investigates the communication experiences of international graduate students in academic, social, and daily contexts in the United States. This study utilizes semi-structured face-to-face interviews with three participants to examine the complex challenges that transcend linguistic barriers, encompassing cultural and educational disparities, psychological impediments such as the fear of error, and a diminished sense of belonging. The work outlines various adaptive strategies, including pre-class preparation, the use of digital tools like Grammarly and ChatGPT, peer practice, and the creation of culturally informed social networks. Studies demonstrate that communication ability correlates with emotional confidence, identity formation, and gradual shifts in mindset, including the recognition of errors as learning opportunities. The study underscores the significance of analyzing the interplay of linguistic, psychological, and cultural factors, rather than solely focusing on language barriers in isolation